Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor DPRD Di Kabupaten Enrekang - Wildana Wafika Saifullah; Burhanuddin Burhanuddin; Uhud Darmawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine whether there is an influence of work environment and work discipline on employee performance at the DPRD Office in Enrekang Regency. The research employs a quantitative approach with a descriptive method and constitutes a population study. The sample for this research comprises the entire workforce of 38 individuals at the DPRD Office in Enrekang Regency. Hypothesis testing in this study employs multiple linear regression analysis, yielding the following outcomes: Based on the results of the hypothesis testing using the multiple linear regression analysis, it is demonstrated that both the work environment and work discipline variables concurrently affect employee performance at the DPRD Office in Enrekang Regency. The results of the hypothesis testing also indicate that the work environment has a partial influence on employee performance at the DPRD Office in Enrekang Regency, and work discipline also partially influences employee performance at the DPRD Oficce in Enrekang.